Sources of change in the money stock - Smith, Robert Ayreton Bailey (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
This research provides an historical, theoretical and practical appraisal of exogenous and endogenous money and money creation, with South Africa as the focus of the practical investigation. Monetary theory of recent decades can be categorised as belonging to one of two distinct paradigms: mainstream (neoclassical) or post Keynesian. The mainstream (orthodox) view presents a Euclidian or Cartesian, ergodic, deductive, and axiomatic theoretical interpretation of the world. This is perpetuated through the continued, and inaccurate, depiction in academia of exogenous money creation, the money multiplier concept, asset transformation by banks, imposed alterations to the money stock by central banks and long-run closed system equilibrium models (and associated homogeneity, and long term behavioural assumptions). In the real world, economic agents, structures, institutions and their interrelations are perpetually evolving. The post Keynesian paradigm provides the theoretical framework within which to understand such a world. Unfortunately the necessity for a multiplicity of methods and methodology makes it a paradigm that is currently prohibitively complex, preventing simple exposition. Money creation should, both historically, and according to the analysis conducted, be defined according to the actual source of change in the money stock, that is, credit extension. In a nonergodic world, changes in the stock of money take on a causal role with regard the initiation of productive processes, and thus influence future economic conditions. The simple, although powerful, technique of balance sheet analysis conducted herein provides a detailed method of identification of causal changes in money stock. Within the context of the institutional and structural environment, it clearly demonstrates the residual nature of money m modern economies. This research serves to emphasise the importance of monetary matters for economic management, as well as the important difference between the money creation process and the residual deposit securities. It serves also to discourage the perpetuation of fallacies of money creation, and capabilities of monetary authorities. In South Africa, as in most countries, the central bank can influence the conditions under which borrowers and banks mutually create money, but do not themselves create or distribute money beyond the facilitation of credit extension by banks
Keywords: Money supply -- South Africa; Money -- South Africa; Banks and banking, Central -- South Africa